The Fast Approval and Slow Rollout of Sputnik V: Why Is Russia's Vaccine Rollout Slower than That of Other Nations? - Elza Mikule; Tuuli Reissaar; Jennifer Villers; Alain Simplice Takoupo Penka; Alexander Temerev; Liudmila Rozanova (MDPI AG, 2021)
The emergence of the SARS-CoV-2 pandemic in the beginning of 2020 led to the deployment of enormous amounts of resources by different countries for vaccine development, and the Russian Federation was the first country in the world to approve a COVID-19 vaccine on 11 August 2020. In our research we sought to crystallize why the rollout of Sputnik V has been relatively slow considering that it was the first COVID-19 vaccine approved in the world. We looked at production capacity, at the number of vaccine doses domestically administered and internationally exported, and at vaccine hesitancy levels. By 6 May 2021, more first doses of Sputnik V had been administered abroad than domestically, suggesting that limited production capacity was unlikely to be the main reason behind the slow rollout. What remains unclear, however, is why Russia prioritized vaccine exportation. We provide three hypotheses that may contribute to explaining the slow domestic rollout: a generalized vaccine distrust among the Russian population, a desire to help less technologically advanced nations, and possible geopolitical incentives.